Somatic chromosomal studies in Ocimum basilicum & Ocimum sanctum L. - Archna,; Shivnaz,; Neeraj Tandon,; Anand, (International Journal of Phytomedicine, 2013)
The study of chromosomal number is a parameter commonly used to characterize cytological of a species, and may have implications for cultivar identification. The present study aimed to determining the chromosome number of Ocimum sanctum and Ocimum basilicum L. The survey conducted in the cytogenetic laboratory, department of genetics and plant breeding, CCS University, Meerut. We used seeds of four accessions of Ocimum, obtained from NBPGR, New Delhi were used in the present study. Accessions IC-436153 and EC-338575 are of Basilicum group, while Accessions IC-344638 and IC-344681 belong to Sanctum group. We used seeds of Ocimum basilicum and Ocimum sanctum. After 24 hrs of germination, radical tips were collected and immersed in saturated solution of para-dichlorobenzene (PDB) for about 3h. The material was fixed in freshly prepared Farmer’s fluid ( 3 parts absolute alcohol: 1 part glacial acetic acid) solution for 24 h. After fixation, the material was transferred to 70% alcohol and stored in a refrigerator for long time preservation, until studied cytologically. Microphotographs were taken by digital camera at the magnification 1000X and karyotypes were generated with the computer-based programmers’- Adobe Photoshop, AutoCAD and Microsoft programmer. The measurements of the chromosomes were made with the help of Erma Tokyo objective micrometer. Chromosome measurements were made on – length of each arm, total chromosome length and the position of secondary constriction, F%, DI and TF%. The number of chromosome found for the species Ocimum basilicum was 2n =48 and Ocimum sanctum was 2n =32. The study of chromosome assumes the role as a restriction commonly used in cytological characterization of the species, and may also have implication for cultivars identification.